2022
DOI: 10.1371/journal.pone.0276453
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy and safety of equipment-assisted intravesical instillation of mitomycin C after transurethral resection of bladder tumour in patients with nonmuscular invasive bladder cancer: A meta-analysis

Abstract: Background This review and meta-analysis aimed to systematically evaluate the clinical efficacy and safety of equipment-assisted intravesical instillation of mitomycin C (MMC) in patients with nonmuscular invasive bladder cancer (NMIBC) after transurethral resection of bladder tumour (TURBT). Methods The Embase, PubMed, CNKI, CBM, WANGFANG, VIP, Cochrane Library, and Clinicaltrial.com databases were searched for articles published before April 2022. The experimental group was treated with intravesical instil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Furthermore, several studies have indicated that bladder MMC HIVEC can potentially slow down the progression of the disease in patients who have a slow response to BCG treatment [26]. Additionally, Zhou et al's metaanalysis also supports the notion that HIVEC is more effective in reducing tumor recurrence and progression rates compared to conventional bladder perfusion chemotherapy [27].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, several studies have indicated that bladder MMC HIVEC can potentially slow down the progression of the disease in patients who have a slow response to BCG treatment [26]. Additionally, Zhou et al's metaanalysis also supports the notion that HIVEC is more effective in reducing tumor recurrence and progression rates compared to conventional bladder perfusion chemotherapy [27].…”
Section: Discussionmentioning
confidence: 96%
“…BC is a molecular heterogeneous malignancy (24). According to histopathological staging, the most common type is urothelial carcinoma (25). In the future, the incidence of BC will increase globally due to increased exposure to BC carcinogens and global aging(26).…”
Section: Discussionmentioning
confidence: 99%
“…A mitomicin C (MMC) a Streptomyces caespitosusból izolált, daganatellenes, antifibrotikus [17] és antibiotikus hatással rendelkező, vízben rosszul oldódó antiproliferatív bifunkciós alkilezőszer, amely a DNS-láncokhoz kötődve gátolja a DNS-szintézist [18]. A közismert kemoterápiás szerként történő alkalmazáson (gyomor- [19], mell- [20] és hólyagrák [21]) kívül az MMC-t széles körben alkalmazzák antifibrotikus gyógyszerként szemészeti [22,23] és fej-nyaki [24] műtétek után a hegszövetképződés megelőzésére. Hosszú ideig történő intravénás alkalmazása során mellékhatásként vese-, gyomor-bél rendszeri és csontvelő-károsodást okozhat.…”
Section: New Minimally Invasive Treatment Options In Benign and Malig...unclassified